LITERASI DIGITAL PADA REMAJA DAN TANTANGANNYA - Rince Tatik Juanita, Rince; Fildzah, Zalsabila Putri; Nasrulloh, Naufal Dzaki; Pamungkas, Widya Jati (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2023)
The digital era has brought several changes as a positive effect. However, the digital era brings many adverse effects at the same time, making it a new challenge in human life today. So, there is no choice but to command and direct the technique properly and correctly to achieve the most significant benefit. Therefore, digital literacy activities provide assistance and training, especially on healthy internet, hoaxes, and cyberbullying. This activity method is carried out in several stages, namely, the stage of expressing ideas, the group discussion stage, and reflective discussion. The results of this literacy activity positively impacted the participants, namely that each participant was able to group and understand the proper use of social media, the negative impacts of their use of social media, and how to overcome the impacts of using digital media. Keywords: Healthy Internet Outreach, Hoax, Cyber Bullying